Place and Memory in the Singing Crane Garden - Schwarcz, Vera, 1947- (Book collections on Project MUSE., 2008)
The Singing Crane Garden in northwest Beijing has been the site of several important and cataclysmic events in modern Chinese history. In this poetic and highly personal study of memory, trauma, and cultural renewal, Schwarcz brings to life the complex history of a richly layered corner of China's much traversed yet little known cultural landscape.